The Legal Dilemma of Abortion in Addressing Social Stigma and the Uncertainty of Access to Legal Abortion Services in Indonesia - Selvi Relita Fitri; Evita Isretno Israhadi (Yayasan Adra Karima Hubbi, 2024)
Background. Abortion in Indonesia is a complex legal issue that involves a delicate balance between protecting women’s reproductive rights and adhering to prevailing social and cultural values. While certain legal provisions allow abortion in cases such as medical emergencies or rape, the practical implementation of these policies is often hindered by legal uncertainties, social stigma, and limited access to safe and legal abortion services. Purpose. This article aims to explore the legal dilemmas surrounding abortion in Indonesia, highlight the challenges women face in accessing reproductive health services, and analyze the existing government policies that affect women’s rights in this context. Method. The research adopts a qualitative approach, reviewing relevant legal documents, policies, and case studies to assess the legal framework surrounding abortion in Indonesia. It also examines the social and cultural factors that influence the accessibility and implementation of abortion services. Results. The study reveals that despite legal provisions allowing abortion under specific circumstances, women in Indonesia continue to face significant barriers in accessing safe and legal abortion services. Legal uncertainty, social stigma, and the lack of awareness about reproductive rights contribute to the difficulties women experience in obtaining necessary healthcare. The analysis shows that current policies are insufficient to fully protect women’s reproductive rights and ensure access to safe abortion services. Conclusion. It is crucial to establish clear, equitable policies regarding abortion and reproductive health services. Additionally, public education campaigns are necessary to reduce stigma and increase awareness of women’s rights. Clear regulations, alongside efforts to inform and educate the public, are key to ensuring that women have access to safe, legal, and equitable reproductive healthcare.